TINGKAT KESUKAAN DAN KANDUNGAN GIZI CRACKERS SUBSTITUSI TEPUNG KACANG MERAH DENGAN PENAMBAHAN DAUN KATUK UNTUK IBU MENYUSUI - Mayka Permatasari; Veni Indrawati (Jurnal Gizi dan Pangan Soedirman, 2022)
Red beans and katuk leaves are plants that have many health benefits, especially for nursing mothers. There is an opportunity to develop functional food products for breastfeeding mothers that are made from these plants. In general, crackers are made with wheat flour, to increase the nutritional content of crackers, it can be done by replacing some of the basic ingredients with other ingredients, namely red bean flour. The research conducted was experimental research in the form of formula development by providing treatment in the form of red bean flour substitution and the addition of katuk leaves on crackers to determine the effect of treatment on hedonic quality and nutritional content. The study was conducted with 6 treatments, namely the proportion of red bean flour: katuk leaves F1 (20%: 5%); F2 (30% : 5%); F3 (40% : 5%); F4 (20% : 10%); F5 (30% : 10%); F6 (40% : 10%). The F3 treatment with 40% red bean flour substitution and the addition of 5% katuk leaves was the most preferred and had the highest average value from the hedonic quality aspect. The proportion of red bean flour substitution and the addition of katuk leaves affect the color, aroma, texture, and taste of crackers. Analysis of nutritional content including protein, carbohydrate, and calcium content of 100 g of selected treatment crackers showed protein content of 17.96%, carbohydrates 68.11%, and calcium 95.80 mg.